Distribution Pattern of Magnetic Susceptibility Value of Iron Sand on the Surface of Pasia Jambak Beach Pasia Nan Tigo Padang - Riza Rahmayuni; Hamdi Rifai; Letmi Dwiridal; Ardilla Nofri Yuwanda; Dwi Anisa Visgus; Anisa Rahmi (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2021)
Iron sand is a natural resource in Indonesia that can be utilized based on magnetic mineral content (Fe203, Fe3O4, FeTiO3), to be processed into materials of high economic value. Iron sand magnetic mineral distribution was analyzed to see potential in Pasia Jambak Beach, Pasia Nan Tigo, Padang, where the iron sand in this area has not been fully utilized by the community and government. The potential of iron sand can be seen usiing Magnetic Method with a magnetic chaaracteristic test in the form of the susceptibility value of iron sand. Magnetic susceptibility value iron sand on the surface of Pasia Pantai Jambak varies betwen 485,2 × 10-8 m3/kg up to 13077 × 10-8 with an average 3.306, 37 × 10-8 m3/kg.. The results of the contour map show that high-value magnetic susceptibility values ​​are scattered near the estuary, namely Muaro Anai and Muaro Baru, this is because magnetic minerals (Fe203, Fe3O4, FeTiO3) which have high density are more likely to settle near the estuary, then the rest spreads to the coast.